Improved Electrochemical Performance of NTs-WS2@C Nanocomposites for Lithium-Ion and Sodium-Ion Batteries - Wei, Shuangying; Serra, Marco; Mourdikoudis, Stefanos; Zhou, Huaijuan; Wu, Bing; Děkanovský, Lukáš; Šturala, Jiří; Luxa, Jan; Tenne, Reshef; Zak, Alla; Sofer, Zdeněk (ACS applied materials & interfaces, 2022)
Even though WS2 nanotubes (NTs-WS2) have great potential as anode materials for lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) thanks to their unusual layered structure, their conductivity and cycling stability are far from satisfactory. To tackle these issues, carbon-coated WS2 (NTs-WS2@C) nanocomposites were prepared through a facile synthesis method that involved precipitating a carbon precursor (20% sucrose) on WS2 nanotubes, followed by annealing treatment under an argon environment. Thanks to the presence of highly conductive and mechanically robust carbon on the outer surface, NTs-WS2@C nanocomposites show improved electrochemical performance compared with bare NTs-WS2. After 60 cycles at 80 mA g-1 current density, the cells display high capacities of 305 mAh g-1 in LIBs and 152 mAh g-1 in SIBs, respectively. As the current density increases to 600 mA g-1, it provides specific capacities of 209 and 115 mAh g-1, correspondingly. The enhanced electrochemical performance in LIBs and SIBs is primarily attributed to the synergistic effects of the tubular architecture of WS2, carbon network and stable nanocomposite structure, which can effectively constrain volume variation during the metal ions intercalation/deintercalation processes.
Keywords: sodium ion batteries; tungsten disulfides; nanotubes; anode; carbon coating; lithium ion batteries